(untitled) (Research, Society and Development, 2025)
Plant diseases are caused by a variety of organisms. Among these, fungi stand out as the most diverse group of phytopathogens. The species Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. is one of the main etiological agents of anthracnose, a phytopathology that affects a vast number of plants worldwide, especially those of agronomic interest. The use of plant-based products has been the focus of several studies in recent years due to their benefits compared to agrochemicals. Therefore, the present study aimed to verify the antifungal activity of the ethanolic extract of Azadirachta indica A. Juss leaves on the in vitro growth of C. gloeosporioides. Furthermore, the levels of chlorophylls, carotenoids, flavonoids, anthocyanins, and total phenolic compounds were determined in the extract and in the dried and fresh samples. For in vitro analysis, four defined concentrations of the ethanolic extract were added to the PDA culture medium and poured into Petri dishes with five replicates for each treatment. Control treatments were also used. In this study, metabolite extraction was more effective in the ethanolic extract than in the other samples for all variables, indicating that the use of ethyl alcohol as a solvent provides a more complete extraction. Regarding the extract’s activity on the fungal species, the results indicate that it did not inhibit their in vitro growth and development at the concentrations tested.